Fonctionnement des tombes du début du Bronze final (XIVe – XIIe s. av. J.C.) dans le sud-est du bassin parisien (France) - Stéphane Rottier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The “disturbed” aspect of graves on many sites of the European Bronze Age has for the most part been interpreted as the result of looting. In the light of the observations made at Barbuise—La Saulsotte “Frécul” and Barbey “Les Cent Arpents”, the possibility of post-sepulchral practices to recover bones from graves, apparently according to a very organised process, should henceforth be taken into account. Eleven states of burial were defined as a result of taphonomic examinations. These functioned as stages of the burial process, depending upon the durability of the structure and its suitability for re-use. The intersection of a maximum of criteria has enabled a new interpretation of these graves, which would otherwise be considered to have been looted.  For several sites it is now possible to attempt reinterpretation of the excavation data.